(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
What can the performing arts do at that moment? The image is that of a boat adrift in the ocean, in which the crew celebrates their luck (or is it death?), in a collective pact in the counterflow of life. With this image, reflecting the Brazilian political moment, I analyze Caranguejo Overdrive, directed by Marco André Nunes, with dramaturgy by Pedro Kosovski. It is interesting to investigate the reasons why it was censored in 2019 and the relevance of the debate on art and historical memory. For this, I use the concept of “entre-lugar” in Latin American discourse, developed by Silviano Santiago, in an article from the 70s, and revisit forty years later, indicating to a spiral of time, in which the play calls us to return to our mangrove, revolving our traces and reinventing the time that comes.